Patient Experience after Mechanical Heart Valve Replacement Surgery at Central General Hospital Haji Adam Malik Medan - Teti Hariani Pane; Dudut Tanjung; Refli Hasan (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Overall postoperative quality of life improves in patients undergoing mechanical mitral valve replacement. Heart valve replacement surgery is the definitive treatment for heart valve abnormalities. Patients undergoing heart surgery will experience mental and physical difficulties after leaving the hospital. Support is an important factor that a person needs when facing health problems. The aim of this study was to explore the experiences of patients undergoing mechanical heart valve replacement surgery to find better treatment plans. This type of research is qualitative research with a descriptive phenomenological approach. The participants in this study were 13 people who were patients who had undergone mechanical heart valve replacement surgery. This research was conducted in June-August 2023 at the Haji Adam Malik General Hospital. The data collection method uses in-depth interviews and research data is analyzed using the Colaizzi method. There are 5 themes identified, namely 1) Patients experience an improvement in their health condition after mechanical heart valve replacement surgery 2) Patients experience sleep disturbances 3) Patients experience anxiety regarding possible complications that occur after mechanical heart valve replacement surgery 4) Patients comply with the home care plan, and 5) Family support in efforts to maintain health after undergoing mechanical heart valve replacement surgery. The research results showed that the majority of participants reveal physical changes, namely complaints before surgery has reduced or disappeared completely but experiences sleep disturbances due to pain, anxiety. Participants also expressed their willingness to follow the treatment plan at home with support from the family. It is especially recommended that cardiovascular nurses involve the family to provide support in efforts to optimize the patient's health status after mechanical heart surgery.Keywords: Heart valve disease, Mechanical heart valve replacement surgery, Patient experience